Development Center For Digital Government Cooperation Patterns Of Small Medium Enterprises-Private To The Acceleration Of Economic Increase In Tourist Areas - Joko Suyono; Nyoman Sudapet (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
The infrastructure budget reached Rp 290 Billion in APBN-P (Budget spending Revenue State changes) in 2015 be consist of opportunities for investors and Government Areas, this will be trigger an increase in the central area of UKM. 2014 year Indonesia stock exchange noted the value of market capitalization (market cap) to the property sector, real estate, and construction of the building reached Rp 360 Billion (idx, 2014). Bank Indonesia survey showed a significant increase in the selling price of units of strata title in Jabodetabek and Bandung, Banten segment of Office, retail, industrial, land and condominiums as well as commercial property rental rates increased and the price of the hotel star 3, 4 and 5 (BI, 2014). Autonomous region through Act No. 22/1999 and no. 34/2004 demanding pemerintah progoverment province, city creative increase revenue areas. BUDGETS (Revenue Budget spending Area) year 2013 deficit financial area reached Rp 54.217 trillion (Kemendagri, 2013). The development of the digital hub of Micro, small, and medium enterprises (UMKM) area can be a collaboration between Central Government, local governments, State-Owned Enterprises, Local, and private sector.